The Effect of Economic Variables on Banking Credits: An Empirical Study of Algeriancommercial Banks (1997-2017) - Fouzi, Abderzag (European Journal of Economics and Business Studies, 2018)
The study aimed to test the effect of deposits, real interest rate, population and economic reforms on the Banking credit fromAlgeriancommercial banks represented by the size of credit facilities. The study used annual data for the period from 1997 to 2017. Where the Multi regression model was estimated using a method of Ordinary Least Squares OLS. Results of the analysis showed that there is a positive relationship with a statistically significant between the credit facilities and the deposits and the variable of economicreforms, while the real interest rate and population size have been linked by significant negative relationship.